Risk factors for early suspected ventilator-associated pneumonia in severe thoracic blunt trauma patient: A French national cohort study - Gary Duclos; Victor Vidal; Noemie Resseguier; Mathieu Boutonnet; Thomas Botrel; Gerard Audibert; Manon Séguret; Vincent Legros; Caroline Jeantrelle; Anh Dao Phan; Olivier Langeron; Elisabeth Gaertner; et al. (PLoS ONE, 2025)
Background Ventilator-associated pneumonia (VAP) is the most common infection in severely injured patients requiring mechanical ventilation. Chest trauma has been identified as a significant risk factor for VAP. This study aimed to describe the risk factors for early VAP in patients with severe blunt thoracic trauma admitted to the intensive care unit (ICU) and receiving mechanical ventilation. Materials and Methods A retrospective cohort study was conducted using data from a national registry including data from 17 French trauma centers during a period of seven years. The study included patients with severe blunt thoracic trauma requiring invasive mechanical ventilation. Data analysis focused on identifying independent risk factors for early suspected VAP (occurring within 48 hours to 5 days after ICU admission) using two models of logistic regression. Results From 31700 patients screened 712 patients were analyzed. Early suspected VAP occurred in 192 (27%) patients. The study identified several independent risk factors associated with early suspected VAP in patients with severe blunt thoracic trauma: male gender (OR= 2.77, 95%CI: 1.68–4.77, p < 0.001), ASA score >1 (OR= 1.64, 95%CI: 1.08–2.50, p = 0.019), injury severity score (ISS) >15 (OR=3.15, 95%CI: 1.13–11.99, p = 0.025), initial Glasgow Coma Scale (GCS) score <9 (OR=2.71, 95%CI: 1.88–3.96, p < 0.001), absolute thoracic abbreviated injury scale (AIS) (OR=1.51, 95%CI: 1.14–1.99, p = 0.003), and the number of packed red blood cells (PRBCs) transfused within the first 24 hours (OR=1.04, 95%CI: 1.00–1.08, p = 0.027). Prehospital antibiotic administration was identified as a protective factor (OR=0.54, 95%CI: 0.29–0.94, p = 0.028). Conclusion In patients with severe blunt chest trauma receiving invasive mechanical ventilation, male gender, ASA score, ISS > 15, GCS < 9, thoracic AIS and number of PRBCs transfused were independent risk factors for early suspected VAP. Prehospital antibiotic therapy was a protective factor, suggesting potential strategies for VAP prevention.